Proliferative activity in endometrial stromal granulocytes throughout menstrual cycle and early pregnancy. Issue 1 (January 1989) - Pace, D; Morrison, L; Bulmer, J N
Abstract : The proliferative activity in endometrial stromal granulocytes was studied using two approaches. Firstly, mitotic activity was studied in paraffin wax embedded sections of normal non-pregnant endometrium and early pregnancy decidua stained with phloxine-tartrazine. Secondly, the monoclonal antibody Ki67 was applied to cryostat sections of similar tissues. Endometrial stromal granulocytes were identified by their labelling with NKH1, Dako T11, UCHL1 or Dako-LC. The percentage of cases in which endometrial stromal granulocytes showed mitosis was 25%, 75%, 86%, and 93%, respectively in proliferative, early secretory, mid secretory, and late secretory phases, and 14% in early decidua. There were at most one or two endometrial stromal granulocytes in mitosis per 10 high power fields. Double labelled cells were present in small numbers in proliferative endometrium and in moderate numbers in secretory endometrium. Only a few cells in early decidua double labelled with Ki67/T11; moderate numbers of cells double labelled with Ki67/Dako-LC. It is concluded that proliferative activity does occur in endometrial stromal granulocytes and is particularly prominent in the late secretory phase.